Review of the Tegalwaru Weir Design Using the Tyrolean Weir Model and the USBR Model Energy Damper - Pramana, Anselmus Henry; Rizal , Nanang Saiful; Gunasti, Amri (International Applied Science, 2023)
Tegalwaru Dam is a permanent weir located in Sumber Kejayan Village, Mayang District, Jember Regency which serves an irrigation area of 85 Ha. Over time, the Tegalwaru weir, which was built in the Mayang watershed, experienced some damage. Therefore, an assessment of the effectiveness of the Tegalwaru Dam was carried out by constructing a USBR energy dampening building and also planning the type of weir using the Tyrol weir. The aim of this research is to find the planned flood discharge at the Tegalwaru weir by utilizing HEC-HMS software and to be able to plan the weir building using the Tyrol weir and design an appropriate energy dampening building for the weir. From the research results, it was found that the planned flood discharge at the Tegalwaru weir was 150.7 m 3 /sec which occurred on December 24 2014. The planned weir at the Tegalwaru weir used the Tyrol weir type with a filter slope of 20˚ and a filter length of 1 meter with a wide storage channel. 1.6 meters wide and the reservoir channel is 1 meter deep. To reduce energy, use a USBR type IV energy reducer.